Reducing Pandemic Risks at Source : Wildlife, Environment and One Health Foundations in East and South Asia - World Bank; Food and Agriculture Organization of the United Nations (Washington, DC: World Bank, 2022)
The majority of human infectious diseases are of animal origin, and many recent emerging infectious diseases (EIDs), such as HIV/AIDS, the Nipah virus, severe acute respiratory syndrome (SARS), highly pathogenic avian influenzas (HPAIs), and Ebola virus disease share a common feature: their wildlife origin. Wildlife-originated EIDs are also increasing in frequency over recent decades. As shown by the ongoing COVID-19 pandemic, the impacts of EIDs disproportionately affect the poor and other vulnerable groups, increasing inequality and threatening decades of development progress. The acceleration of EID events of epidemic and pandemic potential calls for a paradigm shift in how we manage and interact with our natural and built environments, while stressing the urgency to develop and implement comprehensive One Health approaches to achieve optimal health outcomes. Furthermore, it is important to recognize the interconnections between people, animals, plants, and their shared environments. East and South Asia, renowned global hotspots for disease emergence, have suffered from and continue to experience major economic impacts from outbreaks. A team comprised of experts from the World Bank and FAO, and leading wildlife and One Health experts from around the world have worked together to analyze the causes. This report outlines the risks of EIDs of wildlife origin and proposes how to reduce emerging pandemic threats at their source; it includes background material, state-of-the-art knowledge, and recommendations for strengthening systems to prevent, detect, and manage EID outbreaks caused by wildlife trade, wildlife farming, food systems, and habitat degradation. Furthermore, it examines the scope of existing policy frameworks, institutional mandates, level of multisectoral engagement, investments, wildlife-health information systems, and capacity building related to wildlife in the context of emerging disease risks.